2017
DOI: 10.1038/sc.2016.195
|View full text |Cite
|
Sign up to set email alerts
|

Burden of care in primary caregivers of individuals with spinal cord injury in Iran: its association with sociodemographic factors

Abstract: The burden of care among the caregivers of SCI individuals is a multidimensional issue. The sociodemographic characteristics of individuals with SCI and their caregivers can affect the caregiver's burden. Many of these factors can be modified to reduce the burden of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…43% of the caregivers had primary school education. Khazaeipour [ 40 *] 2017 163 SCI ZARIT 44.20 Mean age of the patients: 36 ± 12.5 years Gender of the patients: 32 women and 131 men Duration of suffering from the illness: 76.5 ± 79 months Marital status of the patients: 56.5% married, 38% single, and 5.5% divorced Mean age of the caregivers: 38.1 ± 13.2 years Duration of caregiving: 69.4 ± 73.1 months Gender of the caregivers: 61 men and 102 women Bamari [ 41 *] 2016 70 Diabetes ZARIT 44.14 Gender of the patients: 40 women and 30 men Gender of the caregivers: 36 women and 34 men 70% of the caregivers were wives or husbands of patients. Vahidi [ 42 *] 2016 150 Cancer ZARIT 34.71 Gender of the caregivers: 73 women and 77 men Mean age of the caregivers: 39.6 ± 13.8 years 34.7% of the caregivers were wives or husbands of patients.…”
Section: Resultsmentioning
confidence: 99%
“…43% of the caregivers had primary school education. Khazaeipour [ 40 *] 2017 163 SCI ZARIT 44.20 Mean age of the patients: 36 ± 12.5 years Gender of the patients: 32 women and 131 men Duration of suffering from the illness: 76.5 ± 79 months Marital status of the patients: 56.5% married, 38% single, and 5.5% divorced Mean age of the caregivers: 38.1 ± 13.2 years Duration of caregiving: 69.4 ± 73.1 months Gender of the caregivers: 61 men and 102 women Bamari [ 41 *] 2016 70 Diabetes ZARIT 44.14 Gender of the patients: 40 women and 30 men Gender of the caregivers: 36 women and 34 men 70% of the caregivers were wives or husbands of patients. Vahidi [ 42 *] 2016 150 Cancer ZARIT 34.71 Gender of the caregivers: 73 women and 77 men Mean age of the caregivers: 39.6 ± 13.8 years 34.7% of the caregivers were wives or husbands of patients.…”
Section: Resultsmentioning
confidence: 99%
“…For family educational needs, it is important to consider that SCI not only hampers individuals with SCI, but also have significant impact on families and caregivers as well. 31,32 It brings physical, mental, financial, as well as social dysregulations and thereby has a ripple effect.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of burden placed on the caregiver can manifest them self as physical and emotional stress, burnout, fatigue, anger, resentment and depression among caregivers. 31 Therefore, there is a need to educate them on issues relating to these changes and maintaining a good rapport with them.…”
Section: Discussionmentioning
confidence: 99%
“…The SCI is one of the chronic diseases that cause caregiver burden in healthcare providers (10). Studies have shown that perceived caregiver burden is significant among the caregivers of these patients (9,11,12). The caregiver burden can be an essential and influential risk factor for abuse (13).…”
Section: Introductionmentioning
confidence: 99%